Traumatic Birth and Chronology of Losses - Barazi, Faida; Shlomo, Izhar Ben (British Journal of Healthcare and Medical Research, 2025)
This study examines the impact of traumatic birth experiences on parents of children with cerebral palsy. Background: Traumatic births affect 9-45% of women, potentially causing significant psychological consequences. Objectives: To investigate the losses experienced by parents following traumatic deliveries and their impact on family dynamics and identity. Methods: Twenty-four parents (21 mothers, 3 fathers) from diverse backgrounds in northern Israel participated in qualitative interviews analyzed through thematic and narrative approaches. Results: Six domains of loss emerged: idealized birth experience, autonomy during labor, initial bonding, normative family structure, financial stability, and health security. Parents experienced profound identity disruption while navigating between idealized expectations and the reality of raising a child with special needs. Conclusions: Traumatic births create a domino effect that necessitates reconstruction of family life and self-perception. These findings highlight the need for comprehensive support systems for affected families, addressing both immediate and long-term consequences of traumatic birth experiences.